2012
DOI: 10.1248/bpb.b12-00407
|View full text |Cite
|
Sign up to set email alerts
|

A Rat Model for Stable Chronic Obstructive Pulmonary Disease Induced by Cigarette Smoke Inhalation and Repetitive Bacterial Infection

Abstract: To develop a stable chronic obstructive pulmonary disease (COPD) model in rats. Sprague-Dawley rats were treated with cigarette-smoke inhalation (CSI) for 12 weeks, repetitive bacterial infection (RBI) for 8 weeks, or the combination of the two (CCR) for 12 weeks and followed up for the additional 20 weeks. Tidal volume (V T ), peak expiratory flow (PEF) and 50% V T expiratory flow (EF 50 ), histological changes in the lungs, and levels of the cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-8, and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 42 publications
1
68
0
1
Order By: Relevance
“…( 12 , 21 , 22 ) Li et al adopted a two-step exposure protocol whereby animals were initially exposed to smoke from 8 cigarettes twice a day for 2 weeks (weeks 1 and 2) and subsequently exposed to smoke from 15 cigarettes three times a day for another 10 weeks (weeks 3-12). ( 23 ) The animal model used in the present study simulates the pathophysiological conditions of active smoking, animals having been exposed to mainstream cigarette smoke daily (7 days a week) for 30 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 12 , 21 , 22 ) Li et al adopted a two-step exposure protocol whereby animals were initially exposed to smoke from 8 cigarettes twice a day for 2 weeks (weeks 1 and 2) and subsequently exposed to smoke from 15 cigarettes three times a day for another 10 weeks (weeks 3-12). ( 23 ) The animal model used in the present study simulates the pathophysiological conditions of active smoking, animals having been exposed to mainstream cigarette smoke daily (7 days a week) for 30 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…( 12 , 21 , 22 ) Li et al adotaram um protocolo de exposição dividido em duas etapas: primeiramente, os animais foram expostos à fumaça de 8 cigarros duas vezes por dia durante 2 semanas (semanas 1 e 2) e, em seguida, foram expostos à fumaça de 15 cigarros três vezes por dia durante 10 semanas (semanas 3-12). ( 23 ) O modelo animal usado no presente estudo simula as condições fisiopatológicas do tabagismo ativo; os animais foram expostos à fumaça principal do cigarro diariamente (7 dias por semana) durante 30 semanas.…”
Section: Discussionunclassified
“…Tobacco smoking is the most important risk factor for COPD [2, 4] and the most common COPD-inducer employed in in vivo studies [12]. In addition, to mainstream cigarette smoke, environmental cigarette smoke may also contribute to respiratory symptoms and COPD [4].…”
Section: Cigarette-smoke (Cs)mentioning
confidence: 99%
“…Development of COPD is slow and progressive, with occasional exacerbations caused by inflammatory responses induced by triggering substances such as noxious gases, bacteria or viruses [2]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that airway inflammation induced by viral pathogen-associated molecular pattern stimulation is similar to that in COPD [39], and that cigarette smoke exacerbates airway inflammation induced by viral pathogen-associated molecular patterns [40]. In addition, it has been reported that latent adenoviral infection exacerbates airway inflammation and emphysematous lesions caused by cigarette smoke [41], and that simultaneous exposure to cigarette smoke and bacteria results in the formation of lesions similar to those in COPD [42]. Furthermore, it has been elucidated that CXCL13 is involved in lymphoid follicle formation in the airways of COPD patients as well as in response to viral infections [43,44].…”
Section: Co-evolution Of the Immune System And Microorganismsmentioning
confidence: 99%